Stroke Code Implementation in A Physician-Led District Hospital in Malaysia - Che Isa, Zainura; Lim, Jo Anne; Lee, Aik Kheng; Chan, Yong Chieh; Kang, Huan Yean; Ibrahim, Aznita (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: The past few years have shown a marked improvement in acute ischaemic stroke (AIS) thrombolysis therapy in Malaysia. We analysed our data on stroke code activation performed in a non-neurologist hospital. Methods: Data of all stroke code activated patients from September 2019 to September 2020 was collected. Demographic, clinical characteristics and outcomes of these patients were analysed and reviewed with published data in Malaysia. Results: Seventy cases were stroke code activated. Majority of the stroke cases (80%) were ischaemic in nature with the highest subgroups of lacunar infarct at 60.7%. Hypertension is the most prevalent risk factor followed by dyslipidaemia and diabetes. The median time for onset-to-door was 95minutes, door-to-CT was 24minutes, door-to-decision was 46.5 minutes and door-to-needle was 80minutes. There was a sequential reduction in median door-to-CT and door-to-needle time to 16.5 and 65.5minutes respectively. Fifteen patients (21.4%) were given thrombolysis therapy. The median NIHSS score was 7.5 on arrival and 6 upon discharge. They had an improvement of mRS from a median of 4 upon discharge to 1 at six months follow-up. There were no haemorrhage incidences post thrombolysis. The outcome of LACI strokes versus non-LACI strokes was similar at 3 and 6-months follow-up despite non-LACI strokes having a more severe presentation upon admission. Conclusion: With AIS thrombolysis therapy, non-LACI strokes may have similar functional outcomes as LACI strokes. With backup support from hospitals with neurologists and neurosurgeons, physician-led AIS thrombolysis therapy is implementable in a non-neurologist centre. Strong adherence to protocol is pertinent to ensure success.